Obesity interventions in Egypt: identifying gaps and highlighting assets - Shahin, Hana (AUC Knowledge Fountain, 2015)
Worldwide, obesity is a growing epidemic and a leading non-communicative disease. Egypt has high levels of obesity, causing harm to both individuals and society at large. Data on obesity in Egypt includes measures of obesity rates, comorbidity, and consequences, but there is little documentation on obesity interventions. This is in large part due to the fact that obesity is overlooked by the Egyptian government and culture. This study aimed to collect data on available programs and interventions in Egypt, to explore assets and challenges to obesity programming, and to ask for recommendations for combatting obesity. Semi-structured interviews were conducted with 25 participants from 22 different organizations in Cairo, including ministries, governmental, non-governmental, international organizations, and for-profit organizations. The results showed that there was a lack of nationwide programs and services that tackle obesity; however, there were some minor activities and services that tackled other health issues related to obesity. In terms of challenges, most participants mentioned negative cultural customs and practices or circumstances that affected and contributed to the increase in obesity, such as poverty, personal habits, and environmental and political influences. As for assets, participants mentioned tangible assets such as facilities, finances, and staff; yet, they focused on non-tangible assets such as partners, networks, knowledge, expertise and experience, reputation, media, and support. Participants recommended collaboration, partnerships and multi-sectorial programs on a mass scale including national campaigns to get obesity recognized and on the national agenda. These Recommendations can help develop prevention strategies that are tailored to the socio-cultural and economic context of Egypt.